Engaging with Bediuzzaman Said Nursi a Model of Interfaith Dialogue. - Markham, Ian S. (Farnham : Ashgate Pub., 2009)
Too often interfaith dialogue is generic and unfocused. Often it involves 'liberals' from each tradition coming together to criticize the 'conservatives' in their own traditions. This book provides a model for interfaith dialogue that challenges very directly the 'dialogue industry'. This book involves a Christian theologian in deep conversation with a Muslim theologian. Bediuzzaman Said Nursi (1877-1960) was born at the end of the Ottoman Empire and lived through the emergence of an aggressive secular state. He had to think through, in remarkably creative ways, the challenge of faith within a.
13 Conservatives and Dialogue: Why It Is Essential to Get Conservatives Excited about the Dialogue14 Neither Conservative nor Liberal: A Theology of Christian Engagement with Non-Christian Tradition; 15 Conclusion; Index.
Description based on print version record.
Keywords: Christianity and other religions -- Islam; Islam -- Relations -- Christianity; Dialogue -- Religious aspects -- Christianity; Dialogue -- Religious aspects -- Islam; Nursi, Said, -- 1873-1960.; Nurculuk; RELIGION / Christian Life / Social Issues; RELIGION / Christianity / General; BODY, MIND & SPIRIT / Gaia & Earth Energies; Electronic books